An In Vitro Study on Impact of Environmental Stresses on Growth, Morphological and Biochemical Features of Listeria monocytogenes PTCC 1297 - Samaneh Kazemi; Mohammad Faezi-Ghasemi (Pasteur Institute of Iran, 2015)
Introduction: Listeria monocytogenes is a serious concern for the food industry due to its high case fatality rate, widespread distribution, ability to survive a wide variety of food processing conditions, and the severity of the illness associated with this pathogen infection. The objective of this study was to determine the growth, cell morphology and biochemical characteristics of L. monocytogenes PTCC 1297 (Serotype 4a) under selected environmental stresses. Method: The environmental stresses were acid stress (HCl, pH 2.0-6.0), alkaline stress (NaOH, pH 8.0-12.0), ethanol stress (5.0%-25.0% vol/vol), oxidative stress (H2O2, 0.06%-6.0% vol/vol), osmotic stress (NaCl and sucrose, 2.0%-30.0% wt/vol) and heat stress (40-60°C). All stresses were applied to the exponential phase bacteria whereas non-stressed exponential phase cells served as a control and the cells were allowed to grow for 24 h. For evaluating the growth of L. monocytogenes PTCC 1297 after inoculation procedure and exposure of cells to selected stresses we used colony count method. Scanning electron microscopy (SEM) was implemented to visualize the external appearance of the bacteria. Results: According to the results, the bacteria at pH≤4 and pH≥10 achieved by HCl and, NaOH, respectively, died. Also, concentrations ethanol at ≥15% vol/vol, H2O2 ≥0.3% vol/vol, NaCl ≥14% wt/vol, and heat ≥50°C were lethal for the bacteria. Unlike other stresses, sucrose did not kill bacteria but decreased their growth. The phenotypical and biochemical characteristics of them changed when exposed to each stress. Conclusion: Different doses of various stresses were either lethal or sub-lethal for this bacterium and lead to various changes in its characteristics.